PENGARUH IMPLEMENTASI KEBIJAKAN APLIKASI E-OFFICE ASN TERHADAP EFEKTIVITAS KERJA PEGAWAI DI DINAS KOMUNIKASI DAN INFORMATIKA, PERSANDIAN DAN STATISTIK KABUPATEN SUMEDANG - Garmana, Deden Haria; Maisyaroh, Fuji Dwi; Muhtadi, Asep Saiful; Nureza, Dea Siti; Fatchinnafis, Resthi; Nugraha, Yordian; Nurazizah, Zia (LPPM UNSAP & FISIP UNSAP, 2024)
Relationship between the Implementation of ASN E-Office Policy and the Work Effectiveness of Employees in the Communications and Information, Coding and Statistics Services, Sumedang Regency. The method used in preparing Administrative Research Practices (PPA) is a descriptive analysis method. This research variable uses variables that will be measured from an independent variable of policy implementation and a dependent variable of employee work effectiveness. What was used as a population for this researcher were all ASN employees in the Sumedang Regency Communication and Informatics, Coding and Statistics Service, totaling 35 employees and a sample of 35 people was taken. The method used is literature study, field study (questionnaire, observation).Based on the results of implementation research, the effect of policy implementation is 87.4% (very good) of the ideal criteria with a total score of 1531, and employee work effectiveness is 86.4% (very good) of the ideal criteria with a total score of 1513, the relationship between policy implementation and Work Effectiveness Employees are at a very good correlation level with a correlation coefficient of 0.834. And the influence of policy implementation on the work effectiveness of employees at the Sumedang Regency Communication and Informatics, Coding and Statistics Service obtained a coefficient of determination value of 69.5%, while the side of 30.5% was influenced by other factors that were not examined (eplison factors)